The Influence of Environment and Motivation on Work Discipline of Elementary School Teachers - Vina Okta Viana; Soedjono Soedjono; Aryo Andri Nugroho (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Work discipline is an essential element of human resource management and a prerequisite for achieving optimal teacher performance. However, preliminary findings in several public elementary schools in the Singorojo District indicate that some teachers still exhibit low levels of discipline in terms of attendance and completion of administrative tasks. This condition suggests the presence of underlying factors affecting teacher discipline, particularly the work environment and work motivation. This study aims to analyze the influence of the work environment and work motivation, both partially and simultaneously, on the work discipline of elementary school teachers. The research employed a quantitative approach with a survey design. The population consisted of 266 elementary school teachers in Singorojo District, and a sample of 160 teachers was selected using proportional sampling. Data were collected through questionnaires and analyzed using descriptive statistics, as well as prerequisite tests (normality, linearity, multicollinearity, and heteroscedasticity), and simple and multiple linear regression analyses. The findings indicate that the work environment has a significant influence on teacher work discipline (R² = 0.336). Work motivation also significantly affects work discipline (R² = 0.246). Simultaneously, the work environment and work motivation contribute 40.1% to teacher work discipline (Sig. 0.000). A supportive work environment and high work motivation are proven to enhance the work discipline of elementary school teachers. These findings underscore the importance of enhancing the work environment and bolstering teacher motivation as key strategic efforts for schools. Future research is recommended to explore other potential predictors such as leadership, organizational culture, or workload.